Efektivitas Hukum Pencabutan Hak Dipilih terhadap Koruptor Dalam Pemberantasan Korupsi - Baumi Syaibatul Hamdi (Universitas Islam Indonesia, 2018)
Corruption is an endless problem in Indonesia. Judging from its practice, corruption is often identified with the abuse of authority or power for personal gain. The issues raised in this study are, first, how is the revocation of the rights to be elected in the perspective of laws and regulations? Second, how is the effectiveness of revocation of the rights to be elected in eradicating corruption? This study aims to analyze the effectiveness of the law of revocation of the rights to be elected against corruptors in eradicating corruption. The analysis is described through the statutory approach and conceptual approach. This study concludes, first, revocation of the rights to be elected against corruptors is one of criminal sanctions and an effective effort in eradicating corruption and does not constitute a violation of human rights. Criminal law, human rights law and the Corruption Act provide legitimacy to revoke the rights to be elected against corruptors. Second, the effectiveness of the law on revocation of such rights has a deterrent and prevention effects. Revocation of selected rights has become a necessity for judges to make revocation of chosen rights as a standard imposing sanctions for corruptors in the context of eradicating corruption.Corruption is an endless problem in Indonesia. Judging from its practice, corruption is often identified with the abuse of authority or power for personal gain. The issues raised in this study are, first, how is the revocation of the rights to be elected in the perspective of laws and regulations? Second, how is the effectiveness of revocation of the rights to be elected in eradicating corruption? This study aims to analyze the effectiveness of the law of revocation of the rights to be elected against corruptors in eradicating corruption. The analysis is described through the statutory approach and conceptual approach. This study concludes, first, revocation of the rights to be elected against corruptors is one of criminal sanctions and an effective effort in eradicating corruption and does not constitute a violation of human rights. Criminal law, human rights law and the Corruption Act provide legitimacy to revoke the rights to be elected against corruptors. Second, the effectiveness of the law on revocation of such rights has a deterrent and prevention effects. Revocation of selected rights has become a necessity for judges to make revocation of chosen rights as a standard imposing sanctions for corruptors in the context of eradicating corruption.